PENGARUH SEDIMENTASI TERHADAP KAPASITAS TAMPUNGAN PADA AKHIR UMUR EFEKTIF (T50) WADUK KARIAN - Dhanang Samatha Putra (TEKNISIA, 2019)
Karian Reservoir is one of The National Strategic Projects. Located in Lebak Regency, Banten Province, Karian Reservoir has 207.48 Mm3 effective storage, 46.4 Mm3 dead storage and 50 years lifetime.  In the dam management, one of the problems that often occurs is sedimentation. To overcome this problem, we need to know the sedimentation rate and  distribution pattern of Karian Reservoir for optimalizing the reservoir management. To predict the distribution pattern of the reservoir we use Empirical Area Reduction Methods. The findings of the study show that the sediment volume of the reservoir throughout its effective life is 86.50 Mm3, the new zero elevation is +37.2 m, the remaining dead storage is 7.62 Mm3 and the  remaining effective storage is 167.19 Mm3. This indicates that theoretically the reservoir will work well up to its effective life but the dam sedimentation management must be planned because sediment not only deposit on the dead storage but also on effectife storage.